PELAYANAN PUBLIK PENGURUSAN IZIN MENDIRIKAN BANGUNAN DI KECAMATAN MANDAU OLEH DINAS TATA KOTA, TATA RUANG DAN PEMUKIMAN KABUPATEN BENGKALIS - Hendry Andry (UIR Press, 2018)
This research was designed to analyze public service of building permit management in Mandau District by City Palanning, Spatial Planning an Residence Depertement of Bengkalis Regency. The type of this research was descriptive survey and used quantitative method. The population and sample consisteol ot two groups, the 22 employees of city planning, Spatial Planning and Residence Departement of Bengkalis Regency and the 50 people whom managed the building permissions. The techniques of collecting data were by providing questionnaires, interviews and observations. There were six numbers of indicators in research. This research concluded that The Public Service of building permit management in Mandau District that did by City Planing, Spatial Palnning and Residence of Bengkalis was in category Good Enaugh.